(untitled) (Medical Forum Monthly, 2022)
Objective: To determine the frequency of erectile dysfunction in patients with benign prostatic hyperplasia. Study Design: Descriptive Study Place and Duration of Study: This study was conducted at the Department of Urology, Jinnah Postgraduate Medical Centre (JPMC), Karachi, Pakistan for a period of six months from April, 2020 to October, 2020. Materials and Methods: It was possible to include everyone who met the inclusion criteria and visited JPMC Karachi. It was only after an explanation of the study's risks and benefits that informed consent was obtained. Five items were included in the questionnaire. Data was calculated using SPSS version 23.0. Results: Mean ± SD of age was 54.9±8.4 years. In distribution of obesity, 71 (64%) were obese while 40 (36%) were non-obese. Diabetes mellitus was documented in 43 (38.7%) patients. Erectile dysfunction was documented in 21 (18.9%) patients. Conclusion: It is to be concluded that erectile dysfunction is fairly common in patients with benign prostatic hyperplasia. Furthermore, our findings outline the need for future research to investigate those factors that could be considered as higher risk of erectile dysfunction